2017
DOI: 10.18632/oncotarget.17227
|View full text |Cite
|
Sign up to set email alerts
|

Critical analysis of the major and ancillary imaging features of LI-RADS on 127 proven HCCs evaluated with functional and morphological MRI: Lights and shadows

Abstract: PurposeTo report a critical analysis of major and ancillary MR imaging features in assessment of HCC.MethodsRetrospectively we evaluated 70 cirrhotic patients with 173 nodules, which were subjected to MR study at 0 time (MR0), after 3 (MR3) and 6 months (MR6) using two different contrast media. EOB-GD-DTPA was injected at MR0 and MR6, while Gd-BT-DO3A at MR3. Three expert hepatic radiologists reviewed all images, recording, according to LI-RADS, the size, the presence and quality of arterial-phase hyperenhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 47 publications
(63 citation statements)
references
References 49 publications
2
61
0
Order By: Relevance
“…The striking difference in LR‐4 categories between the two MRIs was that nine (9.5%) HCCs showed APHE on ECA‐MRI but not on HBA‐MRI, which might be partly responsible for the lower diagnostic performance of HBA‐MRI . This could be explained by the small dosage of HBA‐MRI, which is one‐fourth that of conventional ECA (0.025 versus 0.1 mmol/kg) .…”
Section: Discussionmentioning
confidence: 96%
“…The striking difference in LR‐4 categories between the two MRIs was that nine (9.5%) HCCs showed APHE on ECA‐MRI but not on HBA‐MRI, which might be partly responsible for the lower diagnostic performance of HBA‐MRI . This could be explained by the small dosage of HBA‐MRI, which is one‐fourth that of conventional ECA (0.025 versus 0.1 mmol/kg) .…”
Section: Discussionmentioning
confidence: 96%
“…25 Granata et al found that in addition to major imaging features of LI-RADS, hyperintensity on T 2 -weighted images as well as restricted diffusion have a high positive predictive value for HCC. 12 …”
Section: Version 2017 Li-radsmentioning
confidence: 99%
“…Various types of locoregional therapies are available for HCC, such as thermal ablation (eg, radiofrequency ablation, microwave ablation), transcatheter therapies (with or without chemotherapeutic agents), as well as localized radiotherapy. Currently, this algorithm is not designed for systemic therapy or, unless the recurrence is at the surgical margin, in postoperative cases 12 …”
Section: Li-rads V2017 Treatment Responsementioning
confidence: 99%
See 2 more Smart Citations